The Effect Of Tax Avoidance And Corporate Governance On Company Value (Empire Study On Manufacturing Companies In The Consumer Goods Industry Sector Listed On The Indonesia Stock Exchange (Idx) 2015-2018 Period) - Mayangsari, Anisa; Cahyana, Agus; Mulyana Dali, Rahmat; A. Syukur, Dudung (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2022)
This research is based on the  fact  that an investor who wants to invest in their shares sees the  value of the company. This   study aims   to examine: 1)  The effect   of tax   avoidance   on firm   value, 2)   The effect    ofl    corporate   governance   on                                                     firm     value. This type oflresearch is quantitative research. The population of this research is manufacturing companies in the consumer goods industry  which  are listed  on  the  Indonesia   Stock  Exchange   (BEI)   for   the   2015-2018   period.   The   sampling   technique in this study was purposive sampling. The data of this study used financial report data and annual reports obtained by 34 companies with a research period of 4 years and 37 outlier data so that the total sample size was 99 research data. The type of data used is secondary data obtained from www.idx.co.id and www.sahamok.com. The analytical test used is multiple linear regression analysis with the statistical analysis   test   method   using   the   SPSS   version   26   software   program.   The  results showed that: 1) Tax avoidance has a positive effect on firm value. 2) Corporate governance with indicators: The Board of Directors has a negative effect on firm value, the proportion of the Independent Commissioner has no negative effect on company value and the Audit Committee has a positive effect on firm value.